Chemical, thermal and pH-induced equilibrium unfolding studies of fusarium solani lectin - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The effect of urea, guanidine thiocyanate, temperature and pH was studied on the conformational stability of Fusarium solani lectin. Equilibrium unfolding with chemical denaturants showed that the lectin was least stable at pH 12 and maximally stable at pH 8.0 near its pI ( 8.7). Guanidine thiocyanate ( the concentration of denaturant at which the protein is half folded, D-1/2 = 0.49 M at pH 12) was found to be an eight times stronger denaturant than urea (D-1/2 = 3.88 M at pH 12). The unfolding curves obtained with fluorescence and CD measurements showed good agreement indicating a monophasic nature of unfolding and excluded the possibility of formation of any stable intermediate. The effect of pH on the lectin was found to be unusual as at acidic pH, the lectin showed a flexible tertiary structure with pronounced secondary structure, and retained its hemagglutinating activity. On the other hand, the lectin did not show any loss of conformation or activity upto 70 degrees C for 15 min. Moreover, thermal denaturation did not result in the aggregation or precipitation of the protein even at high temperatures. Thermal denaturation was also carried out in the presence of a low concentration of guanidine thiocyanate. Change in the enthalpy of transition (Delta H-m) varied linearly with transition temperature (T-m), which indicated that the heat capacity (Delta C-p =3.95 kJ (.) mol(-1) (.) K-1) of the lectin remained constant during the unfolding.
Keywords: Denaturation; Fusarium solani; guanidine; Lectin; thermal; Unfolding